The reporting quality of parallel randomised controlled trials in ophthalmic surgery in 2011: a systematic review - Yao, A C (Eye (Lond), 2014)
PURPOSE: Randomised controlled trials (RCTs) represent a gold standard for evaluating therapeutic interventions. However, poor reporting clarity can prevent readers from assessing potential bias that can arise from a lack of methodological rigour. The Consolidated Standards of Reporting Trials statement for non-pharmacological interventions 2008 (CONSORT NPT) was developed to aid reporting. RCTs in ophthalmic surgery pose particular challenges in study design and implementation. We aim to provide the first assessment of the compliance of RCTs in ophthalmic surgery to the CONSORT NPT statement. METHOD: In August 2012, the Medline database was searched for RCTs in ophthalmic surgery reported between 1 January 2011 and 31 December 2011. Results were searched by two authors and relevant papers selected. Papers were scored against the 23-item CONSORT NPT checklist and compared against surrogate markers of paper quality. The CONSORT score was also compared between different RCT designs. RESULTS: In all, 186 papers were retrieved. Sixty-five RCTs, involving 5803 patients, met the inclusion criteria. The mean CONSORT score was 8.9 out of 23 (39%, range 3.0–14.7, SD 2.49). The least reported items related to the title and abstract (1.6%), reporting intervention adherence (3.1%), and interpretation of results (4.7%). No significant correlation was found between CONSORT score and journal impact factor (R=0.14, P=0.29), number of authors (R=0.01, P=0.93), or whether the RCT used paired-eye, one-eye, or two-eye designs in their randomisation (P=0.97). CONCLUSIONS: The reporting of RCTs in ophthalmic surgery is suboptimal. Further work is needed by trial groups, funding agencies, authors, and journals to improve reporting clarity.